GW24-e2907 Effects of RG7652, a fully human mAb against proprotein convertase subtilisin/kexin type 9, on LDL-c: a Phase I, randomised, double-blind, placebo-controlled, single- and multiple-dose study. (1st October 2013) - Tingley, Whittemore; Luca, Diana; Leabman, Maya; Budha, Nageshwar; Kahn, Robert; Baruch, Amos; Cowan, Kyra; Davis, John C
Abstract : Objectives: Proprotein convertase subtilisin/kexin type 9 (PCSK9) regulates hepatic LDL receptors, playing a key role in cholesterol metabolism. Gain of function genetic mutations cause autosomal dominant hypercholesterolaemia, while nonsense mutations lower LDL-c and the risk of coronary events. RG7652 (MPSK3169A) is a fully human IgG1 monoclonal antibody (mAb) directed against PCSK9. This first-in-human study evaluated safety, tolerability, pharmacokinetics, pharmacodynamics, and efficacy in healthy individuals with elevated LDL-c. Methods: This Phase I study tested single and multiple doses of RG7652 and placebo given subcutaneously to 80 healthy volunteers with elevated serum LDL-c concentrations. Subjects entered six ascending, single-dose (SD) and four multiple-dose (MD) cohorts allocated 6 active: 2 placebo. Two MD cohorts included atorvastatin therapy (40 mg daily) prior to administration of study drug. Following cohort safety reviews, escalation to the next higher dose cohort continued. The primary efficacy endpoint was change in LDL-c 2 weeks after final dose of study drug, with safety follow-up occurring during Weeks 8–16. Results: Eighty subjects (mean age 45 years, range 19-64; 48% male) with mean LDL-c of 162 mg/dL (4.2 mmol/L) were randomised. RG7652 reduced mean LDL-c by as much as 90 mg/dL (60%) from baseline, with a dose-dependent effect that appeared to saturate at the highest doses. The average reduction in LDL-c at Day 15 in SD and Day 36 in MD was > 40 mg/dL in all cohorts other than the lowest dose. RG7652 had similar LDL-c lowering effects and kinetics when added to atorvastatin. No dose-limiting safety effects were identified and no subjects discontinued study drug for adverse events (AEs). Thirty-seven AEs, all mild, were attributed to study drug: 27 in 14 RG7652 subjects; 10 in 6 placebo subjects. Conclusions: The anti-PCSK9 mAb, RG7652, safely decreased LDL-c in healthy volunteers with elevated LDL-c as monotherapy and in combination with atorvastatin. The results support further testing of RG7652 in dyslipidaemic patients.